A Multidimensional Analysis of Pakistani English Written Discourse - Isra Irshad; Behzad Anwar (Linguistics and Literature Review, 2021)
The present study analyzes Pakistani English written discourse through multidimensional analysis. For this purpose, two corpora types, including Pakistani universities’ newsletters and Pakistani human rights NGOs’ annual reports, have been complied. It has been investigated how the language of newsletters of Pakistani universities differs from that of annual reports of Pakistani human rights NGOs on D1 and D2 of the multidimensional approach. Biber’s (1988) multidimensional analysis provides the theoretical grounding to the present study. MAT software (1.3) has been used to tag and analyze the data. Co-occurrences of linguistic features are quantitatively analyzed and then qualitatively interpreted through D1 and D2 of multidimensional approach. The results reveal that the language of this written discourse of Pakistani English is informational on D1. By comparing it with Biber’s work of 1988, it has been revealed that this genre is close to the official documents on D1. The language of Pakistani universities’ newsletter is more informational on this dimension than that of the genre of Pakistani NGOs annual reports as the mean scores for both are -26.79 and -25.13, respectively. The analysis of the D2 indicates that the genre of the selected written discourse is non-narrative. However, Pakistani universities’ newsletters are close to broadcasts, whereas the annual reports of human rights NGOs are close to the personal letters. Moreover, the newsletters discourse is strongly non-narrative than that of the annual reports. Keywords: Linguistic variation; Pakistani English; written discourse, Biber’s approach, Multidimensional analysis; linguistic patterns; co-occurrence